DETERMINANTS OF EMPLOYEE RETENTION AT SINTESA PENINSULA HOTEL MANADO - Tambajong, Clinton Franklin; Saerang, David P.E; Pandowo, Merinda . (Universitas Sam Ratulangi, 2018)
Abstract : In every company there will always be employees who run the company, therefore companies are trying to retain employees to stay in a longer period of time. The aim of this research is to identify the determinants of employee retention at Sintesa Peninsula Hotel Manado. This research is quantitative type of research which uses primary data obtained through questionnaire and uses Confirmatory Factor Analysis (CFA) as the analytical tool. The population of this research are 145 employees where the sample size is taken from 100 employees. There are 20 variables that defined as factors that influence employee retention at Sintesa Peninsula Hotel Manado. The analysis and discussion from this research there are 16 variables that correlated with the factor that already conducted. The findings from the factor analysis process there are 4 factors that influence employee retention at Sintesa Peninsula Hotel Manado. First factor is Employee Performance with seven independent variables. Second factor is Employee Engagement with three independent variables. Third Factor is Employee Productivity with four independent variables. And fourth factor is Motivation with two independent variables. The result shows that Sintesa Peninsula Hotel Manado needs to maintain and improve those four important factors to reach employee retention.Â Keywords : employee retention, confirmatory factor analysis.